1984
DOI: 10.1073/pnas.81.23.7476
|View full text |Cite
|
Sign up to set email alerts
|

Specific stimulation of actin gene transcription by epidermal growth factor and cycloheximide.

Abstract: Stimulation of quiescent AKR-2B mouse embryo cells with epidermal growth factor (EGF) results in a rapid and specific induction of actin mRNA sequences. These mRNAs include those coding for both P-and y-cytoskeletal, but not a-skeletal muscle, actin isotypes. Elongation of nascent RNA chains in isolated nuclei (run-off transcription) demonstrates that the mRNA accumulation is preceded by an increase in actin gene transcription. This increase is transient, however, and is followed by a rapid attenuation of tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
98
2

Year Published

1987
1987
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(111 citation statements)
references
References 38 publications
11
98
2
Order By: Relevance
“…Furthermore, this induction is prevented by a mutation in the MRE. It has been reported that the endogenous muscle actin gene is not induced by a serum growth factor (11). The discrepancy between this previous report and these data may result from differences in expression that result from the episomal rather than chromosomal location of the muscle gene, from species differences, or because a sensitive RNase protection assay was employed in these experiments to measure transcript levels.…”
Section: Srecontrasting
confidence: 74%
“…Furthermore, this induction is prevented by a mutation in the MRE. It has been reported that the endogenous muscle actin gene is not induced by a serum growth factor (11). The discrepancy between this previous report and these data may result from differences in expression that result from the episomal rather than chromosomal location of the muscle gene, from species differences, or because a sensitive RNase protection assay was employed in these experiments to measure transcript levels.…”
Section: Srecontrasting
confidence: 74%
“…By 3-4 hr the entire set ofgenes was nearly inactive again. This response is similar to that of the c-fos and actin genes (9,31). The response of gene 3CH482 (like the kinetics of RNA accumulation) resembles that of the c-myc gene (see Fig.…”
Section: Methodssupporting
confidence: 55%
“…Accumulation of actin mRNA in regenerating liver occurs as soon as 1 h after partial hepatectomy and could be related to the G0/G1 transition, as described in AKR-2B mouse embryonic cells [21]. The late phase (included in the 3 -24-h post-hepatectomy period) of actin, c-myc and topoisomerase-I mRNA accumulation is on the contrary clearly related to the hepatocyte proliferation, since it is not observed after a sham operation or after Freund's adjuvant injection.…”
Section: Discussionmentioning
confidence: 82%